2018
DOI: 10.3390/geosciences8070237
|View full text |Cite
|
Sign up to set email alerts
|

Geomechanical Model Test and Energy Mechanism Analysis of Zonal Disintegration in Deep Surrounding Rock

Abstract: Abstract:With the decreasing of shallow resources, underground roadways of resources exploitation have reached into deep rock mass with high geostress. A series of new failure phenomena such as zonal disintegration phenomenon were discovered in deep surrounding rock, which is completely different from shallow caverns. To reveal the formation mechanism of zonal disintegration, the geomechanical model test and energy mechanism analysis of zonal disintegration were carried out respectively. Taking the deep roadwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…With its advantages of visualization, intuition and realism, the geomechanical model test is of great significance to the study of damage mechanism of underground caverns (Chen et al 2013a(Chen et al , 2013b(Chen et al and 2013cZhang et al 2013 andGao et al 2018). The method can also simulate excavation and unloading under real three-dimensional high ground stress conditions, reproduce the damage pattern of the cavern, and capture the variations in deformation and stress (Zhang et al, 2019a(Zhang et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%
“…With its advantages of visualization, intuition and realism, the geomechanical model test is of great significance to the study of damage mechanism of underground caverns (Chen et al 2013a(Chen et al , 2013b(Chen et al and 2013cZhang et al 2013 andGao et al 2018). The method can also simulate excavation and unloading under real three-dimensional high ground stress conditions, reproduce the damage pattern of the cavern, and capture the variations in deformation and stress (Zhang et al, 2019a(Zhang et al, , 2019b.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the failure features of the surrounding rock and the rationality of supporting methods accurately, many similar simulation tests and numerical experiments were conducted in the past few years [13][14][15][16][17][18]. Gao et al [16] studied the oscillation law of rock displacement under excavation unloading through a 3D geomechanical model test and proposed a new energy failure criterion. Lin et al [17] researched the deformation, stress, and failure of roadway surrounding rock under the high geostress through a geomechanical model test and found that local rockburst occurred within the roadway.…”
Section: Introductionmentioning
confidence: 99%
“…Structural features such as faults, joints, interlayer slippage zones, and pelletization dissection are usually well developed and are considered to be other types of main structure plane in red beds, such as the interlayer slippage zone (a structurally related feature) of red beds located in southwestern China [26] and faults or fractures at the depth of red beds in the South Georgia Rift (SGR) basin [27]. It is well known that rock mass structures play a dominant role in the stability of a rock mass [11,16,28]. The characteristics of slope failures in red beds are summarized from field investigations and case studies as follows:…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that rock mass structures play a dominant role in the stability of a rock mass [11,16,28]. The characteristics of slope failures in red beds are summarized from field investigations and case studies as follows:…”
Section: Introductionmentioning
confidence: 99%